2010
DOI: 10.1152/ajpendo.00374.2010
|View full text |Cite
|
Sign up to set email alerts
|

Prepubertal urinary estrogen excretion and its relationship with pubertal timing

Abstract: Whether prepubertal estrogen production impacts on the timing of puberty is not clear. We aimed to investigate prepubertal 24-h estrogen excretion levels and their association with early and late pubertal markers. Daily urinary excretion rates of estrogens of 132 healthy children, who provided 24-h urine samples 1 and 2 yr before the start of the pubertal growth spurt [age at takeoff (ATO)], were quantified by stable isotope dilution/GC-MS. E-sum3 (estrone + estradiol + estriol) was used as a marker for potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…For all urine samples, uN and uK measurements had to be available as major selection criteria. The different age ranges for female and male adolescents were chosen to account for the earlier puberty onset in girls (24). Because of possibly incomplete collection, urine samples with a 24-h creatinine excretion rate ,0.1 mmol/ (kg body weight × d) (22) were excluded.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…For all urine samples, uN and uK measurements had to be available as major selection criteria. The different age ranges for female and male adolescents were chosen to account for the earlier puberty onset in girls (24). Because of possibly incomplete collection, urine samples with a 24-h creatinine excretion rate ,0.1 mmol/ (kg body weight × d) (22) were excluded.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…A longitudinal study in girls revealed that urinary estrogen levels 1 or 2 years prior to the pubertal growth spurt predicted earlier thelarche and menarche (0.9 and 0.3 years respectively) (6). Additionally, insulin and insulinlike growth factor 1 (IGF1) could also modify breast development by promoting breast cell division as it has been observed in adults (7,8,9).…”
Section: Introductionmentioning
confidence: 97%
“…Circulating oestrogens are elevated in young women with early menarche (Shi et al, 2010) and this early exposure to oestrogen may be responsible for the increased risk of breast cancer in women with early menarche over and above the increased risk associated with menstrual cycling (Collaborative Group on Hormonal Factors in Breast Cancer, 2012). Fluctuating ovarian hormones presumably create a pro-tumourigenic environment in the mammary gland that, over time, increases the risk of cancer.…”
Section: Introductionmentioning
confidence: 99%